Moderate degradation does not preclude microarray analysis of small amounts of RNA - Oliver Schoor; Toni Weinschenk; Jörg Hennenlotter; Stefan Corvin; Arnulf Stenzl; Hans-Georg Rammensee; Stefan Stevanović (BioTechniques)
Gene expression analysis by microarrays using small amounts of RNA is becoming more and more popular against the background of advances and increasing importance of small-sample acquisition methods like laser microdissection techniques. The quality of RNA preparations from such samples constitutes a frequent issue in this context. The aim of this study was to assess the impact of different extents of RNA degradation on the expression profile of the samples. We induced RNA degradation in human tumor and healthy tissue samples by endogeneous ribonucleases. Next, we amplified 20 ng total RNA degraded to different extents by two rounds of in vitro transcription and analyzed them using Affymetrix oligonucleotide microarrays. Expression differences for some genes were independently confirmed by real-time quantitative PCR. Our results suggest that gene expression profiles obtained from partially degraded RNA samples with still visible ribosomal bands exhibit a high degree of similarity compared to intact samples and that RNA samples of suboptimal quality might therefore still lead to meaningful results if used carefully.